Impacts of vitrification on the transcriptome of human ovarian tissue in patients with gynecological cancer - Gu, Ruihuan; Ge, Naidong; Huang, Bin; Fu, Jing; Zhang, Ying; Wang, Ningyi; Xu, Yan; Li, Lu; Peng, Xiandong; Zou, Yaoyu; Sun, Yijuan; Sun, Xiaoxi (Frontiers in Genetics, 2023)
Abstract Objective: This present study aimed to investigate the effects of vitrification/warming procedure on the mRNA transcriptome of human ovarian tissues. Design: Human ovarian tissues were collected, and processed foe vitrification (T group) then subjected to RNA-sequencing (RNA-seq) analysis, HE, TdT-mediated dUTP nick-end labelling (TUNEL) and real-time quantitative PCR were performed, and the results were compared to those of the fresh group (CK). Results: A total of 12 patients, aged 15 to 36 years with a mean anti-Müllerian hormone level of was 4.57 ± 3.31 ng/mL, were enrolled in this study. According to the HE and TUNEL results, vitrification could effectively preserve the human ovarian tissue. A total of 452 significantly dysregulated genes (|log2FoldChange| > 1 and P<0.05) were identified between the CK and T groups. Among these, 329 were up-regulated and 123 were down-regulated. A total of 372 genes were highly enriched for 43 pathways (P < 0.05), which were mainly related to systemic lupus erythematous, cytokine-cytokine receptor interaction, the TNF signalling pathway, the MAPK signalling pathway, etc. IL10, AQP7, CCL2, FSTL3, and IRF7 were significantly up-regulated (P < 0.01), while IL1RN, FCGBP, VEGFA, ACTA2, and ASPN were significantly down-regulated in the T group (P < 0.05), compared to in the CK group, which was agreed with the results of the RNA-seq analysis. Conclusions: The results showed, for the first time, to the authors’ knowledge, that vitrification can induce the changes in mRNA expression in human ovarian tissues. Further molecular studies on human ovarian tissues are required to determine whether altered gene expression could result in any downstream consequences.